(untitled) (The International Journal for Scientific Research, 2023)
The study aimed to find out the effectiveness of the proposed training program in the development of research skills among secondary school science teachers and the reflection of the impact of the program on the development of scientific thinking among their students in Taif. In order to achieve this goal, the researcher used a semi-empirical approach with experimental design, consisting of a single group and two tests (pre/post), the researcher has proposed the construction of the training program, a test of the research skills for science teachers and a measure of the scientific thinking of students. After verifying the veracity of the program and the validity and reliability of the test and measure, the study was applied to two samples: the first sample of secondary school science teachers and their number reached (45 teachers) in these three disciplines (Chemistry, Physics, and Biology). They were presented the proposed training program. Their pre and post performance was measured by a scientific research skills test. The second sample is second secondary and thread grade students, who have been taught by teachers who attended the training program and their number reached (204 students). Their pre and post performance was measured by a scientific thinking scale. The "T" test was used for both correlated and in dependent group, and Pearson correlation coefficient, ETA square, in order to test the hypotheses of the study. The study found a number of results, the most important were that the training program contributed in the development of the scientific research skills of science teachers of the secondary level, where significant differences have been found at the lowest level (α≤0.05) between the average performance of science teachers to the test of scientific research skills as a whole, and these differences were significant in favor of the post application. Also, the training program had an impact on the teachers, and this has been reflected in their students where it has been noticed an increase in the average performance of the students in the post test according to the measure of the scientific thinking skills after that their teachers passed the training program. In light of the results of the study, the researcher recommended several useful recommendations. It also provided a number of suggestions for future research studies that can be a complement to this study.